ON THE APPROACH TO DESIGN OF EDUCATIONAL PROCESS IN A HIGHER EDUCATION INSTITUTION - Бичков О. С. O.B.; Bychkov, O.C. (Journal of Information Technologies in Education (ITE), 2010)
The analysis of events taking place in the dean’s office during the learning process is observed. For the most significant Petri network was built, which is aimed to model them.